Jan Koch, Rikke Agnete Olsen & Jens Vellev (red.): hikuin 19. Festskrift til Hans Stiesdal på 70-årsdagen 6. maj 1992. (Forlaget Hikuin, 1992). 288 s., 150 kr. - Bøgh, Anders (Historie/Jyske Samlinger, 1993)
-